On Translation and Authorship - Zeller, Beatriz (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2000)
AbstractUsing the concepts of translation and authorship as a starting point, this article explores the role of the literary translator vis-à-vis the cultural forces that determine the acceptance (or non-acceptance) of translation as an original form of expression. A comparison is made of the modern translation traditions of Spanish-America and Anglo-America.